The Contribution of Word-, Sentence-, and Discourse-Level Abilities on Writing Performance: A 3-Year Longitudinal Study - Carvalhais, Lénia; Limpo, Teresa; Pereira, Luísa Álvares (Frontiers in Psychology, 2021)
Writing is a foundational skill throughout school grades. This study analysed the development of different levels of written language (word, sentence, and discourse) and explored the relationship between these levels and writing performance. Ninety-five Portuguese students from two cohorts - Grade 4 to 7 (n = 47) and Grade 6 to 9 (n = 48) - were asked to produce a descriptive text twice, with a 3-year interval. Produced texts were used to assess spelling, syntactic correctness and complexity, and descriptive discourse as well as text length and quality. The main results showed that there were improvements from Grade 4 to 7 and from Grade 6 to 9 in word- and sentence-level skills, along with increases in some dimensions of the descriptive discourse. Moreover, the older cohort performed better than the younger cohort in terms of spelling, syntactic complexity, and text quality, but not in terms of syntactic correctness, one dimension of the descriptive discourse and text length. Regression analyses showed that writing performance was predicted by word and sentence levels in the younger cohort only, and by discourse-level variables in both cohorts. Overall, despite indicating a generalized growth in writing skills throughout schooling, this study also highlighted areas that may need additional attention from teachers, mainly in terms of the descriptive features.